Acute Myocarditis Diagnosed by Layer‐Specific 2D Longitudinal Speckle Tracking Analysis. Issue 1 (6th September 2015) - Caspar, Thibault; Germain, Philippe; Ghannudi, Soraya El; Morel, Olivier; Samet, Hafida; Trinh, Annie; Petit‐Eisenmann, Hélène; Talha, Samy; Fichot, Marie; Jesel, Laurence; Ohlmann, Patrick
Mini‐Abstract: This is a report of a 34‐year‐old patient presenting with acute chest pain, whose diagnosis of acute myocarditis was suspected by layer‐specific longitudinal speckle tracking analysis, showing preferential alteration of subepicardial deformation in the left ventricular lateral wall, and confirmed by cardiac MRI showing late gadolinium enhancement in the subepicardium of the same LV segments.